1989
DOI: 10.1007/bf02471409
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the tolerance of the autotransplanted canine lung against warm ischemia

Abstract: Left lung autotransplantation was performed in mongrel dogs to examine the limitation of tolerance of the deflated lung against warm ischemia in a warm ischemic time (WIT) range of 60-360 minutes. The animals were divided into the 4 following groups according to the duration of WIT and the use of heparin: Group 1; WIT 60-120 min., heparin (-), Group 2; WIT 120-240 min., heparin (+), Group 3; WIT 240-360 min., heparin (+), and Group 4; WIT 240-360 min., heparin (-). All the Group 1 animals tolerated a right pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Palazzo et al [20] demonstrated in a model of left lung ischemia-reperfusion in dogs that a period of 120 min of warm ischemia results in signifi cant lung injury also of the contralateral lung, but this was not at all close to being lethal. These fi ndings are similar to others, which limit the maximum safe warm ischemic period of defl ated lungs to 2 h [6,[21][22][23] . However, all authors investigated lung ischemia at room temperature (20-22 ° C) resulting in signifi cantly lower organ temperatures.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…Palazzo et al [20] demonstrated in a model of left lung ischemia-reperfusion in dogs that a period of 120 min of warm ischemia results in signifi cant lung injury also of the contralateral lung, but this was not at all close to being lethal. These fi ndings are similar to others, which limit the maximum safe warm ischemic period of defl ated lungs to 2 h [6,[21][22][23] . However, all authors investigated lung ischemia at room temperature (20-22 ° C) resulting in signifi cantly lower organ temperatures.…”
Section: Discussionsupporting
confidence: 71%
“…Within this period we found that 90 min of lung ischemia at 37 ° C results in signifi cant and reproducible reperfusion injury in all investigated parameters ( fi g. [3][4][5][6]. Animals of the I-60 group did show lung injury at the start of reperfusion but recovered more and more during the reperfusion period of 2 h ( fi g. 2-4 ).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Yamaz aki et al (17) rep orted in the eanine lung autotransplanta tion model that grafts showing low Pao, immedi ately after reperfusion revealed unsatisfaetory pulmonary funetion on da y 2 or 6 after transplantation. Then, the adequat e Pa a , level of th e transplante d lung immediately after re perfus ion was th ought th e first target.…”
Section: Discussionmentioning
confidence: 98%